Transformasi Literasi Digital Pelajar Madrasah melalui Pelatihan Konten Kreatif di Desa Sukoharjo, Kecamatan Plemahan, Kabupaten Kediri - Alfaruq, Ilham; Permatasari, Vina Septiana; Rahmawati, Isma; Saputri, Melinda Candra; Sari, Lisma Puspita; Setiawan, Ahmad Rendi; Tamama, Jazil Nadiyya; Royhanah, Hikmatur (Fakultas Tarbiyah IAIN Kediri, 2025)
This community service activity aims to strengthen digital literacy, creativity, and the positive identity of students and teachers at Madrasah Tsanawiyah Islamiyah and Madrasah Aliyah Islamiyah in Sukoharjo Village, Plemahan District, Kediri Regency, through a Content Creative Workshop. The activity was conducted on August 2–3, 2025, employing the Participatory Action Research (PAR) approach with the participation of 42 individuals. The training was structured into two main stages: conceptual lectures and hands-on practice in producing educational content, including short videos, digital posters, and creative narratives grounded in madrasah values. Data were collected through participatory observation, in-depth interviews, and evaluation of participants’ works. The findings indicated a significant improvement in students’ technical skills, self-confidence, and understanding of digital ethics. Publishing students’ works via the madrasah’s social media platforms effectively enhanced the institution’s positive image. Therefore, the Content Creative Workshop has proven effective in transforming students from passive users into active and responsible content creators and holds strong potential for replication in other rural madrasahs as a strategy to advance digital literacy.